2022
DOI: 10.3758/s13423-022-02211-z
|View full text |Cite
|
Sign up to set email alerts
|

Tuning social modulations of gaze cueing via contextual factors

Abstract: Gaze cueing reflects the tendency to shift attention toward a location cued by the averted gaze of others. This effect does not fulfill criteria for strong automaticity because its magnitude is sensitive to the manipulation of different social features. Recent theoretical perspectives suggest that social modulations of gaze cueing could further critically depend on contextual factors. In this study, we tested this idea, relying on previous evidence showing that Chinese participants are more sensitive to gazes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
2
3
0
Order By: Relevance
“…The present work represents an additional piece of evidence showing that the modulatory role of a given variable becomes evident when an intermixed, rather than blocked, presentation of different stimuli is adopted, which is in line with some previous studies on the gaze-cueing effect (e.g., Dalmaso et al, 2020a ; Pavan et al, 2011 ; Zhang et al, 2023 ). Additional, albeit indirect, evidence for this notion can also be found in studies examining spatial orientation in response to body pictures depicting individuals with neutral or action-oriented postures (Azarian et al, 2016 , 2017 ).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The present work represents an additional piece of evidence showing that the modulatory role of a given variable becomes evident when an intermixed, rather than blocked, presentation of different stimuli is adopted, which is in line with some previous studies on the gaze-cueing effect (e.g., Dalmaso et al, 2020a ; Pavan et al, 2011 ; Zhang et al, 2023 ). Additional, albeit indirect, evidence for this notion can also be found in studies examining spatial orientation in response to body pictures depicting individuals with neutral or action-oriented postures (Azarian et al, 2016 , 2017 ).…”
Section: Discussionsupporting
confidence: 91%
“…More precisely, the block design adopted in Experiment 1 suggested that our social attention system treated the two types of foot cues similarly. However, and in line with previous studies (Dalmaso et al, 2020a ; Pavan et al, 2011 ; Zhang et al, 2023 ), an intermixed presentation of stimuli could increase the saliency of the action-oriented foot cue over the neutral foot cue, thus favouring the emergence of an orienting response for the former cue. Therefore, this possibility was examined in Experiment 2.…”
Section: Methodssupporting
confidence: 84%
See 2 more Smart Citations
“…This framework postulates that gaze cueing may represent the default behavioural response in the absence of further information about the identity or group membership of the face conveying eye gaze. In this regard, it is now well established that several social features can indeed affect gaze cueing (e.g., Carraro et al, 2017; Dalmaso et al, 2012; Hungr & Hunt, 2012; Liuzza et al, 2013; Slessor et al, 2010; Zhang et al, 2021 see Dalmaso et al, 2020b for a review) and that such modulations are further contingent upon contextual settings (Zhang et al, 2023). Hence, the theoretical proposal is that gaze cueing can be framed as a conditionally automatic phenomenon, namely that it is sensitive to moderating processes.…”
Section: Discussionmentioning
confidence: 99%